ChemInform Abstract: Giant Volume Change and Topological Gaps in Temperature‐ and Pressure‐Induced Phase Transitions: Experimental and Computational Study of ThMo2O8. Issue 15 (24th March 2016) - Xiao, Bin; Kegler, Philip; Gesing, Thorsten M.; Robben, Lars; Blanca‐Romero, Ariadna; Kowalski, Piotr M.; Li, Yan; Klepov, Vladislav; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract: Single crystals of monoclinic ThMo2 O8 are prepared by solid state reaction of Th(NO3 )4 and MoO3 (1273 K, 6 h).